2020
DOI: 10.1111/jace.17039
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired alumina/reduced graphene oxide fibrous monolithic ceramic and its fracture responses

Abstract: Natural composites have very simple compositions and complex hierarchical architectures consisting of several different levels. These features simultaneously endow them with strength, toughness, functional adaptation, and damage‐healing characteristics. Inspired by the microstructural features of natural materials, this work successfully fabricated Al2O3/reduced graphene oxide (rGO) fibrous monolithic ceramics with bamboo‐like structures by introducing a thin graphene oxide around Al2O3 fiber cells to form the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The crack growth resistance was calculated through the J-integral method, and the crack extension length was measured by a compliance method. The detailed calculation was given in our previous paper [11] and the ASTM E1820-05a standard [27]. The typical R-curves of the PcBN/hBN fibrous monolithic ceramics are plotted in Fig.…”
Section: Fracture Characteristics and R-curve Behaviors Of Pcbn/hbn F...mentioning
confidence: 99%
See 2 more Smart Citations
“…The crack growth resistance was calculated through the J-integral method, and the crack extension length was measured by a compliance method. The detailed calculation was given in our previous paper [11] and the ASTM E1820-05a standard [27]. The typical R-curves of the PcBN/hBN fibrous monolithic ceramics are plotted in Fig.…”
Section: Fracture Characteristics and R-curve Behaviors Of Pcbn/hbn F...mentioning
confidence: 99%
“…It consisted of ceramic fiber cells and cell boundaries around the fiber cells, and has been extensively studied because of its great freedom and flexibility for structural design. The long fiber-reinforced structure can endow composite ceramics with non-brittle fracture characteristics and high toughness due to the confluence of extrinsic toughening mechanisms acting on different scales [10,11]. Our previous research demonstrated that Al 2 O 3 /rGO fibrous monolithic ceramics exhibited excellent crack resistance and progressive failure behavior with a high fracture toughness (29.46 MPam 1/2 ) and work of fracture (WOF) (799 J/m 2 ), which are 475% and 1075% higher than those of the monolithic Al 2 O 3 ceramic, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of RGO boundaries between Al 2 O 3 fiber cells resulted in superior friction reduction and wear resistance, with stable friction coefficients. Fracture responses of bioinspired RGO/Al 2 O 3 fibrous monolithic ceramic were also investigated in work ( Chen et al, 2020a ). The investigated nanocomposite was characterized by progressive plastic failure behavior, excellent damage tolerance and high structural reliability due to complex hierarchical architectures with several different levels.…”
Section: On the Rgo/ai 2 O 3 Nanocomposite Systemmentioning
confidence: 99%
“…In particular, a fibrous monolithic ceramic consisting of Al 2 O 3 fibers surrounded by rGO "cell boundaries" shows good strength and outstanding fracture toughness perpendicular to the fiber direction, although not in the parallel direction due to the weak interfaces. [176] A clever structure can also be used to improve this aspect, maximizing adhesion between a reinforcing filler material and its matrix. For instance, the mechanical strength of a Cu-CNT composite for load-bearing can be much improved by changing the geometry of the filler to a leaf-like structure, with a strong and stiff CNT midrib surrounded by GO nanoribbons whose high surface area and hydrophilic functional groups improve the interfacial bonding.…”
Section: Microscopic Imitation Of Bulk Structuresmentioning
confidence: 99%